Otolith morphology as a tool for stock discrimination of three rockfish species in the East Sea of Korea - Park, Joo Myun; Kang, Min Gu; Kim, Jong Hun; Jawad, Laith A.; Majeed, Samroz (Frontiers in Marine Science, 2023)
The shape and structure of otoliths play a vital role in studying fish populations because otolith shape indices are often applied to discriminate fish species. This study focused on examining inter-and intraspecific variations in otolith shape and size among three species of rockfish (Sebastes inermis, Sebastiscus marmoratus, and Sebastes zonatus) collected from the Dokdo and Ulleungdo regions of the East Sea in Korea. A total of 35 S. inermis specimens, 19 S. marmoratus specimens, and 59 S. zonatus specimens were collected between April 2021 and August 2022. The otolith shape was visualized using wavelet coefficients in the shapeR package. Otolith size indices, such as length, width, perimeter, and area, and shape indices, including form factor, aspect ratio, ellipticity, circularity, roundness, rectangularity, and squareness, were calculated for each species. Otolith size and shape indices significantly differed among the three rockfish species (p < 0.05). Compared with the other two species, S. marmoratus possessed more elongated otoliths, whereas S. zonatus had the largest otolith area, perimeter, and length. Average shape analysis based on wavelet coefficients revealed significant differences in otolith shape, particularly on the rostrum and posterior sides. A canonical analysis of principal components (CAP) confirmed the complete separation of otolith shapes among the three rockfish species, with 92.5% of the variation explained by the first axis (CAP1). The findings of this study enhance our understanding of the fish species in the Korean East Sea.